중국 수출확대를 위한 한국 농식품 브랜드 아이덴티티 정립 - 안욱현; 조우철; 김창환; An, Wook-Hyun; Cho, Woo-Chul; Kim, Chang-Hwan (Journal of distribution science, 2014)
Purpose - The purpose of this study is to target Chinese consumers of Korean agri-food through the analysis of agri-food brand identity images to set future directions for proposed agri-food exports to China. Since negotiations began for a free trade agreement (FTA) between Korea and China, some Koreans have worried about the Korean agriculture sector. The world trading system has undergone many changes in recent years. Since the start of FTA negotiations on agriculture, China and Korea have faced a heightened sense of crisis. China is trying to export agricultural products so actively that its agricultural exports could increase by more than 7% annually. China exported about one-tenth of its agricultural products to Korea in the period 2002-2010. Recently, the importance of brand identity has tended to increase, as the world becomes one unified market. In this situation, we should try to promote agri-food exports to China. It is very important to understand consumers' recognition of Korean food and the image of the Korean agri-food industry, to establish an export strategy. Research design, data, and methodology - This study targeted 2,800 adult men and women aged 25-59 years living in four major cities in China (Beijing, Shanghai, Guangzhou, and Qingdao) with a household income within the top 10% level in the China, using the one-to-one interview survey method. In addition, four groups by region (eight people per group) for a total of 32 groups were surveyed by using the focus group interview (FGI) research method, and impressions of imported agri-food were surveyed using 17 questions about fresh agri-food and 22 questions on processed agri-food. Factor analysis, brand positioning, biplot analysis, and so on, were carried out based on the results of these surveys. This research presents the brand identity of Korean food; according to the analyses, the brand identity is based on trust, safety, and attractiveness. Result - Factor analysis results showed that Chinese consumers expect four major qualities in imported fresh agri-food: freshness/safety, attractive appearance, premium branding, and excellent taste/quality. In the case of processed agri-food, it turned out that Chinese consumers are focused on safety/hygiene/freshness, health, and taste. In addition, in the fresh agri-food analysis by country, American foods had the upper hand; the image of American foods was also recognized as the most positive for processed agri-food. Meanwhile, according to the biplot analysis, Korean agri-food is strongly preferred for its appearance, but no country is strongly preferred as regards the level of freshness/safety that is expected by Chinese consumers. Conclusions - In this study, we analyzed the image of imported agri-food expected by Chinese consumers by reconstructing agri-food characteristics from the brand perspective. The research result shows that a Korean brand identity must be the ultimate goal for activities undertaken to enhance the image of Korean agri-food in the future. Additional research is needed because brand image can be formed through various channels.